Flexible prices, labor market frictions, and the response of employment to technology shocks - Federico S. Mandelman; Francesco Zanetti (Federal Reserve Bank of Atlanta, 2013)
Recent empirical evidence establishes that a positive technology shock leads to a decline in labor inputs. Can a flexible price model enriched with labor market frictions replicate this stylized fact? We develop and estimate a standard flexible price model using Bayesian methods that allows, but does not require, labor market frictions to generate a negative response of employment to a technology shock. We find that labor market frictions account for the fall in labor inputs.
Keywords: E32; 330; technology shocks; employment; labor market frictions